1989
DOI: 10.1111/j.1432-1033.1989.tb14547.x
|View full text |Cite
|
Sign up to set email alerts
|

The predicted secondary structures of the nucleotide‐binding sites of six cation‐transporting ATPases lead to a probable tertiary fold

Abstract: Six cation-dependent transporting ATPases have homologous sequences in the region assigned by chemical labelling to nucleotide binding. Comparison of the most highly conserved segments with other nucleotide-binding domains showed that the sequences were consistent with a mononucleotide-binding fold and enabled a number of likely folding topologies to be limited to two or three alternatives. One of these possible folds was topologically equivalent to adenylate kinase; this was taken as a model in which the sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
71
1

Year Published

1989
1989
2007
2007

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(73 citation statements)
references
References 51 publications
1
71
1
Order By: Relevance
“…It has been proposed that Thr-625 in SERCA1a, which is an integral part of the highly conserved TGD motif, might participate in the formation of the nucleotide-binding site (39). Conservative mutations in Thr-625 were shown to result in a Ca 2ϩ transport deficiency and impaired abilities to form a phosphorylated intermediate with ATP or P i (40).…”
Section: Figmentioning
confidence: 99%
“…It has been proposed that Thr-625 in SERCA1a, which is an integral part of the highly conserved TGD motif, might participate in the formation of the nucleotide-binding site (39). Conservative mutations in Thr-625 were shown to result in a Ca 2ϩ transport deficiency and impaired abilities to form a phosphorylated intermediate with ATP or P i (40).…”
Section: Figmentioning
confidence: 99%
“…This cytoplasmic segment is 430 amino acids in length of which, 180 residues comprise the ATP binding domain [9]. As hypothesized, the M4M5 cytoplasmic loop contains the nucleotide-binding site as evidenced by several studies utilizing chemical modification to inhibit ATP hydrolysis.…”
Section: Fluorescein Inhibitionmentioning
confidence: 94%
“…Another interesting approach to this problem is based on the analysis of the folding mechanism of ␤ proteins (5): it has been shown that the number of permissible topologies depends on the number of ␤-strands and on the folding pathway. Furthermore, a number of regularities for ␤-sheet motifs, such as the nonexistence of knots in the chain, has been discovered (15)(16)(17)(18)(19)(20). It has also been shown that loops do not cross (14,21).…”
mentioning
confidence: 99%